THE APPLICATION OF PICTURE WORD INDUCTIVE MODEL (PWIM) TO IMPROVE STUDENTS’ ACHIEVEMENTS IN WRITING DESCRIPTIVE TEXT - Jernih D Sinurat (Journal MELT (Medium for English Language Teaching), 2019)
This study attempted to investigate the application of picture word inductive model (PWIM) to improve students’ achievements in writing descriptive text. The  purpose  of the study  is  to  find  out  whether  PWIM  can  improve  students’  achievement  in  writing  descriptive.  This study was conducted by applying classroom action research. The  subject  of  this  study  was  the  first  year  students  ( X/A)  of  SMA  Swasta Gajah Mada Medan. The data of this research were obtained in two cycles. The instrument used for collecting data was quantitative and qualitative. Based on the writing test result, the students’ score kept improving every test.  The findings indicate that the using of PWIM as a media of learning improved students’ writing achievement. The students’ score significant improvement, the mean of second cycle i.e. 80.28 is higher that the mean of the first cycle i.e. 70.86. Based on diary notes, questionnaire sheet, observation sheet and interview, it was found that teaching learning process ran well. The conclusion is that the using of PWIM as a media of learning improves students’ writing Achievement.